PENGARUH PROMOSI DIGITAL, PENGGUNAAN FITUR LAZPAYLATER, DAN KONTROL DIRI TERHADAP PERILAKU KONSUMTIF PADA PENGGUNA APLIKASI LAZADA DI MEDAN MARELAN - Tumangger, Ismawati (MTU PRESS, 2023)
This research was conducted with the aim of knowing the effect of promotions, lazpaylater features, and self-control on consumer consumptive behavior at the Lazada online shop. The method used in this study is the quantitative method and the data collection techniques carried out are distributing questionnaires, interviews and observations. Respondents in this study were consumers who had purchased goods at the Lazada online shop around Medan. Withdrawal of the number of samples using the slovin formula, then the sample obtained is 100 respondents with α = 0.5 . The results of this study prove that partially the research variables, namely promotions, lazpaylater features and self-control have a significant and significant effect on the consumptive behavior of Lazada online shop consumers. The influence of the promotion variable and the lazpaylater feature are positive and self-control has a negative effect on the consumptive behavior of Lazada online shop consumers. Furthermore, simultaneously or together it gives the result that promotions, lazpaylater features and self-control have an effect and are significant on the consumptive behavior of Lazada online shop consumers